GerAB residues predicted to interfere with water passage based on steered molecular dynamics are key to germinosome functionality - Chen, Longjiao; Beekhuis, Houdijn; van den Bosch, Christina; Vinay, Gianni; Korza, George; Vreede, Jocelyne; Setlow, Peter; Brul, Stanley (Frontiers in Microbiology, 2025)
Some Bacillales and Clostridiales bacteria form spores in unfavorable environments. These spores are dormant but can rapidly resume metabolism in germination. This process can be initiated by a variety of low molecular weight nutrients termed germinants. Structural modeling and mutagenesis studies showed that GerAB, an inner membrane (IM) protein of the Bacillus subtilis spore germinant receptor (GR) GerA, is involved in L-alanine-initiated spore germination. A previous molecular simulation study also suggested there is a water channel in GerAB. In the current work, Steered Molecular Dynamics (SMD) simulations were employed to force a single water molecule through GerAB, identifying three key amino acid residues, Y97, L199 and F342, that interfere with water passage. When these residues were altered to alanine, L-alanine germination no longer occurred in spores with L199A, F342A and triA (Y97A, L199A and F342A triple mutant), while Y97A mutant spores germinated ∼61%. Additionally, except for Y97A, all other mutants showed compromised germination triggered by the AGFK mixture (L-asparagine, D-glucose, D-fructose and K+ ion). Western blotting found reduced levels of the GerA GR in the Y97A mutant, and an absence of the GerA GR in all other mutants. This proves that all three identified residues are crucial to the structural integrity of the GerA germinant receptor and also suggests they are essential for the formation of a fully functional GR complex, the germinosome.